PENGARUH MOTIVASI, KOMPENSASI, LINGKUNGAN KERJA,DAN KOMPETENSI TERHADAP KINERJA PEGAWAI PADA DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KABUPATEN LABUHANBATU - Leily, Novrihan (Universitas Labuhanbatu, 2021)
This study aims to determine work motivation, compensation, work environment, and competence that affect the work performance of employees of the Labuhanbatu Regency Population Control and Family Planning Service. Data collection in this study was conducted through a survey approach with quantitative descriptive research type by distributing questionnaires to 47 respondents, while the population used in this study were employees at the Population Control and Family Planning Office of Labuhanbatu Regency. The data analysis tool used in this study was SPSS (Statistical Product Software Solution). The data analysis technique in this research is descriptive analysis, multiple linear regression analysis, hypothesis testing using partial significance test (t-test), simultaneous significance testing (F test), and determination coefficient testing (R2). The results of this study indicate that partially (t-test) it is known that partially work motivation influences the work performance of employees of the Labuhanbatu Regency Population Control and Family Planning Service with count (3.191)> t table 1.682) and a significance level of 0.003 <0.05. Compensation Partially Affects Employee Work Performance of Labuhanbatu Regency Population Control and Family Planning Office with count (4.904)> t table (1.682) and a significance level of 0.000 <0.05. Partially, the work environment affects the work performance of the employees of the Labuhanbatu Regency Population Control and Family Planning Office with an at-count value of (3.776)> t table (1.682) and a significance level of 0.000 <0.05. Then partially Competence Affects Employee Work Performance of the Population Control and Family Planning Office of Labuhanbatu Regency with the tcount value, namely (4.596)> table (1.682) and a significance level of 0.000 <0.05. In simultaneous testing (F test), it is known that work motivation, compensation, work environment, and competence affect the work performance of employees of the Labuhanbatu Regency Population Control and Family Planning Service with the results of the research showing that the value of Fount is (35.102)> Fable (2.59). and a significance level of 0.00 <0.05.